Orchestration of energy efficiency capabilities in networks. (January 2016) - Riekstin, Ana C.; Januário, Guilherme C.; Rodrigues, Bruno B.; Nascimento, Viviane T.; Carvalho, Tereza C.M.B.; Meirosu, Catalin
Abstract: The energy demand for operating Information and Communication Technology (ICT) systems has been growing, implying in high operational costs and consequent increase of carbon emissions. Both in datacenters and telecom infrastructures, the networks represent a significant amount of energy spending. Given that, there is an increased demand for energy efficiency solutions, and several capabilities to save energy have been proposed. However, it is very difficult to orchestrate such energy efficiency capabilities, that is, coordinate or combine them in the same network, ensuring a conflict-free operation and choosing the best one for a given scenario, ensuring that a capability not suited to the current bandwidth utilization will not be applied and lead to congestion or packet loss. There is neither a way to do this taking business directives into account. In this regard, a method able to orchestrate different energy efficiency capabilities is proposed considering the possible combinations and conflicts among them, as well as the best option for a given workload and network characteristics. The business policies are refined down to the network level in order to bring high-level directives into the operation, and a Utility Function is used to combine energy efficiency and performance requirements. A Decision Tree able to determine what to do in each scenario is deployed in a Software Defined Network environment. The proposed method was validated with different experiments, testing the Utility Function, checking the extra savings when combining several capabilities, the decision tree interpolation and dynamicity aspects. The orchestration proved valid to solve the problem of finding the best combination for a given scenario, achieving additional savings due to the combination, besides ensuring a conflict-free operation. Abstract : Highlights: A method able to orchestrate different energy efficiency capabilities is proposed. It considers the possible combinations and conflicts among the capabilities. It refines business policies to bring high-level directives into the operation. The method solves the problem of finding the best combination for a given scenario. And achieved additional savings, besides ensuring a conflict-free operation.